Forest resource depletion, soil dynamics, and agricultural productivity in the tropics - Ehui, Simeon K.; Hertel, Thomas W.; Preckel, P.V. (Elsevier, 1990)
A two-sector dynamic model for agriculture and forestry is proposed. Agricultural yields are a function of the rate of deforestation, the forest stock, and purchased inputs. We examine the impact of changes in the social discount rate, net returns to agriculture, and direct marginal benefits of the forest stock benefits on the optimal deforestation path under the assumption of a quadratic agricultural yield function. Finally, steady-state comparative static analysis is conducted.